Characterization of the non-covalent docking motif in the isolated reactant complex of a double proton-coupled electron transfer reaction with cryogenic ion spectroscopy - Perez, Evan H. (2020)
The solution kinetics of a proton-coupled electron transfer reaction involving two-electron oxidation of a Ru compound with concomitant transfer of two protons to a quinone derivative have been interpreted to indicate the formation of a long-lived intermediate between the reactants. We characterize the ionic reactants, products, and an entrance channel reaction complex in the gas phase using high-resolution mass spectrometry augmented by cryogenic ion IR photodissociation spectroscopy. Collisional activation of this trapped entrance channel complex does not drive the reaction to products but rather yields dissociation back to reactants. Electronic structure calculations indicate that there are four low-lying isomeric forms of the non-covalently bound complex. Comparison of their predicted vibrational spectra with the observed band pattern indicates that the C=O groups of the ortho-quinone attach to protons on two different -NH2 groups of the reactant scaffold, exhibiting strong O-H-N contact motifs. Since collisional activation does not lead to the products observed in the liquid phase, these results indicate that the reaction most likely proceeds through reorientation of the H-atom donor ligand about the metal center.